Trade in health services and sustainable development - Rupa Chanda (Asian Development Bank Institute (ADBI), 2017)
Effective health services form the backbone of health interventions. Accessibility, quality, capacity, organization, availability of human and physical resources and equity in the provision of health services are essential for a healthcare system to deliver desired health and related sustainable development outcomes. This paper focuses on the impact of health services trade on the realization of sustainable development goals and the various modalities through which this impact may occur. The focus on the intersection of health services and trade is motivated by the growing globalization and tradability of health services due to cross-border investment flows, mobility of health professionals and patients across borders, the use of information and communication technologies to deliver cross-border services and the transfer of ideas, research and management skills and knowhow between countries. The discussion highlights the positive and negative implications of health services trade for sustainable development goals and the fact that this impact depends on the specifics of the country and its national healthcare system, the regulatory environment governing the health sector and related sectors, the policies adopted to facilitate or constrain this trade and the associated externalities. The paper concludes by indicating two broad directions for policy action at the national level, if trade in health services is to facilitate the realization of SDGs and mitigate the negative effects on development. The first is to address structural issues in the healthcare system, the key structural issues being standards, infrastructure, human resources and technology. The second area for policy action is to ensure synergies between health services trade and the rest of the healthcare system. In addition to national policies, multilateral and regional cooperation can also promote sustainable development in the context of health services trade. Overall, the paper suggests that trade in health services can be strategically used to address several sustainable development goals, although it may pose potential challenges for equity and sustainability. Countries need to adopt a proactive approach to provide a supportive regulatory and infrastructural environment so that the many potential gains associated with health services trade can be facilitated and enhanced while the associated negative effects can be minimized or prevented. Trade should therefore not be viewed in a narrow way as a form of commercialization of health services but rather as a means to make health services more accessible, affordable and of better quality.
Keywords: I15; F19; 330; Governance and public sector management; Health; Industry and trade